Duties of Candour in Healthcare: The Truth, the Whole Truth, and Nothing but the Truth?. (21st March 2022) - Quick, Oliver
Abstract: The creation of professional and statutory duties of candour has formalised the requirement for clinicians and healthcare organisations to be honest with patients and families when treatment has gone wrong. This article explains the background to creating both duties, analyses the concept of candour, the role of apologies, and considers evidence about compliance. It argues that making candour a statutory requirement appropriately reflects the ethical imperative of telling the truth about harm and is a powerful signal for honesty. However, being candid is not easy in the context of complex professional cultures, the realities of delivering care in under-funded health systems, and in the shadow of possible legal and regulatory proceedings. Proposals in the current Health and Care Bill to create investigatory 'safe spaces' which prohibit the disclosure of information submitted to the Health Service Safety Investigations Body undermine candour. This article argues against such proposals, which are both wrong in principle and highly problematic in practice. Candour should be respected as a cardinal principle governing not only the conduct of those providing care, but also those who investigate such incidents. Harmed patients and their families deserve to know the whole truth.